If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 15 = 3x + 15 Reorder the terms: 15 + x = 3x + 15 Reorder the terms: 15 + x = 15 + 3x Add '-15' to each side of the equation. 15 + -15 + x = 15 + -15 + 3x Combine like terms: 15 + -15 = 0 0 + x = 15 + -15 + 3x x = 15 + -15 + 3x Combine like terms: 15 + -15 = 0 x = 0 + 3x x = 3x Solving x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. x + -3x = 3x + -3x Combine like terms: x + -3x = -2x -2x = 3x + -3x Combine like terms: 3x + -3x = 0 -2x = 0 Divide each side by '-2'. x = 0 Simplifying x = 0
| 4v*4v= | | 3-14+2(x-9)=2x-2 | | n-9=-81 | | (x-6)(4x+5)=o | | 2r^2-4r+1=0 | | 4(-8x+12)=26-32x | | g(x)=x^3-x+1 | | 8.4t=4.2 | | 5(2w-7)=3 | | 4tan(3x)=5 | | ln(x+4)-ln(x-2)=4 | | 1x+5y=124 | | 4+x=3x-20 | | (x-i)(x+i)=0 | | 1/2n+7=n/14/2 | | 3n-5=-8(6-52) | | (8.8)(-0.9)=7.92 | | 3-3(2x+4)=21 | | 9(w^2+1)=-9 | | x^2+22x+837=0 | | Y+9=-12-y+3 | | -2(m+l)=10 | | 3a-5+2a= | | 2(5a-13)=6(-2a+3) | | -16x^2+15x+12=0 | | 199200(2/x)=150x | | 3x+5+x=-1-2x | | -4.3x-2.2x=13 | | Y=10+0.89*100 | | 22x(45+32)56=1000 | | 0.5+0.5x-1.7x=-0.46 | | 0.5+0.5-1.7x=-0.46 |